Revealing the Miraculous: Objects Placed inside the Statue of the Kōfukuji Nan'endō Fukūkenjaku Kannon - Yen-Yi, Chan (Japanese journal of religious studies, 2022)
The use of relics and gorintō (five-element pagodas) as objects placed in Buddhist statues gained currency in the late twelfth century. This article examines the deposits (nōnyūhin) placed by Fujiwara no Kanezane (1149-1207) in 1189 within the statue of Fukūkenjaku Kannon in the Nan'endō at Kōfukuji in Nara, one of the earliest examples to contain both relics and gorintō. The article unravels the intricate relationship between the contents of the inserted objects, the meaning of the statue, and the motives behind the placing of the deposits. On the one hand, the deposits in this statue were carefully selected to manifest Kanezane's conception of the sacred. On the other, they were intended to evoke a response from Fukūkenjaku Kannon to generate rebirth in Amida's pure land. The relic deposit was enshrined because of its connection to Pure Land rebirth and was to transform the statue into a shōjinbutsu (living buddha) that assumed an array of meanings: an icon containing relics, a nexus for salvation, and a miraculous manifestation of the deity. It is also suggested that Pure Land belief was a driving force behind the increase in using relics as nōnyūhin in the late twelfth century.